Pengaruh Big Five Personality Dan Komitmen Organisasi Terhadap Organizational Citizenship Behavior Karyawan Pada Pt. Indonesia Pratama Di Kecamatan Tabang - Mawardi Mawardi; Sri (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2021)
Abstract: The purpose of this study was to determine whether the big five variables personality and organizational commitment significantly influence organizational citizenship behavior of employees at PT. Indonesia Pratama in Tabang District and to find out, which of these variables has the most dominant influence on organizational citizenship behavior of employees at PT. Indonesia Pratama in Tabang District. The total population in this study amounted to 53 employees in the production section and the number of samples used was 53 employees. The analytical tool in this research is multiple regression. The research results show that the Big Five Personality (X1) and Organizational Commitment (X2) variables simultaneously or collectively have a significant effect on the Employee Organizational Citizenship Behavior variable at PT.Indonesia Pratama in Tabang District. The Big Five Personality (X1) variable has a partial effect on the Organizational Citizenship Behavior of Employees at PT. Indonesia Pratama In Tabang District. Variable Organizational Commitment (X2) partially affects the Organizational Citizenship Behavior of Employees at PT. Indonesi Pratama in Tabang District. From the two partial correlation test results above, it can be seen that the value of the Big Five Personality (X1) variable is the largest compared to the organizational commitment variable (X2), so the Big Five Personality (X1) variable is the most dominant variable influencing the Organizational Citizenship Behavior of Employees at PT. Indonesia. Primary In Tabang District. Keywords: Big Five Personality, Organizational Commitment, Organizational Citizenship Behavior